Transporte público por ônibus e segregação urbana : um estudo sobre acesso a oportunidades em João Pessoa - PB - Dantas, Niara Fernandes Barbosa Formiga (2023)
The production process of segregated cities is a reflection of the accelerated urbanization process occurred in Brazil in the second half of the 20th century, which contributed to the production of sprawling and socially and territorially segregated cities. In this context, the public transportation has the role of integrating different areas of the city and promoting the population's access to urban opportunities, however, it often reinforces segregation even more. Currently, more than 84% of Brazil's population, and 99% of João Pessoa's inhabitants, live in urban areas and the number of cars traveling in the cities has also grown sharply. As a result, the lowincome population is often deprived of accessingthe urban opportunities available. Given this scenario, this work analyzes whether public transportation in João Pessoa contributes to the socio-spatial segregation caused by the urban evolution of the city, based on the application of the accumulated opportunity index. The spatialization of data was carried out by the aiding of a Geographic Information Systems (GIS) tool, by connecting the results to socioeconomic data and urban opportunities in the study area. The study analyzes the ease of accessing jobs, public education and health equipments through public transport by bus, providing simulations for travel times of 15 minutes, 30 minutes, 45 minutes and 60 minutes, by using the private car as a comparative parameter. In João Pessoa, the main urban opportunities are located in the central area of the city, however, it appears that there is a large concentration of the population in the southeast region, especially the low-income population, which is concentrated in the expanded areas of the city. The results obtained in this study suggest that: a) the low-income population residing on the borders of the city accesses fewer opportunities compared to the population located in areas close to the Center and with higher income; b) the usage of private car provides shorter travel times compared to public transportationfor accessing opportunities; c) the areas with higher rates of motorization in the city, which have higher per capita incomes, coincide with neighborhoods where it is possible to access more opportunities in less time. Therefore, the population with higher purchasing power benefits by living in the best locations in terms of accessibility, in addition to being more likely to use the car.